Avaliação de cardápios ofertados em escolas públicas no município de Belém-Pa - PEREIRA, Sabrina de Melo (2023)
Objective: To evaluate the menus offered in public schools in the city of BelémPA. Methodology: a descriptive quantitative and documentary study was carried out, which evaluated menus collected from public elementary schools in the municipality of Belém, during 2018. In the analysis of the menus, Resolution CD / FNDE no. 26/2013 for the classification of fruits and vegetables, the presence of sweet preparations and the quantification of sodium while in the evaluation of foods of sociobiodiversity, the IQ cosan is prohibited and restricted. Results: 49 meals were prepared by the nutritionist, to serve the 200 school days, and 1 weekly menu was simulated. The presence of the group of fruits and vegetables was found on all days of the week, totaling a weekly offer of 337g. Sweet and / or sweet preparations were not present on the annual menu. When assessing the amount of sodium present in the annual menu, of the 49 preparations prepared, 98.88% (n = 46) demonstrated adequacy and in the “simulated weekly menu” assessment, all demonstrated adequacy. Regarding the presence of regional foods and sociobiodiversity, it was noted that of the 49 prepared preparations, 20.4% (n = 10) included these foods and, in the “simulated weekly menu”, with the application of the IQ COSAN tool, it was evident the presence of 2 foods. As for the presence of restricted foods, 49 preparations 16.32% (n = 8) contained them and, there were no prohibited foods. Conclusion: there are deficiencies in the PNAE menus, as the inadequate supply of nutrients compromises the supply of healthy food for students.